(untitled) (Research, Society and Development, 2021)
Introduction: Dermatitis herpetiformis (DH) is a benign, chronic, inflammatory manifestation of the skin. The lesions are erythemato-papular vesicular eruptions, pruritic, symmetrical, herpetiform in shape, and have an affinity for extensor surfaces. It is male-dominant, between the ages of 30 and 40, and is related to abnormalities of the small intestinal mucosa and to IgA deposition in the papillary dermis. It has a multifactorial origin, encompassing genetic, environmental, and immunologic components. Objectives: To analyze the application of knowledge obtained by integrative review addressing dermatitis herpetiformis and celiac disease (CD) to develop a clinical rationale for early diagnosis and effective treatment. Methodology: Scientific and review articles published and referenced in MEDLINE, LILACS, IBECS, BINACIS, LIS, BRISA/RedTESA and MEdCArib were consulted, delimited from 2008 to 2019. The books "Tratado de dermatologia" by Belda Júnior and "Dermatologia" by Sampaio and Rivitti were also included. Results: The diagnosis of DH is clinical, laboratory and immunological. The presentation and eruption activity of the blisters is variable. The classic histopathologic finding is a subepidermal cleft with neutrophils and eosinophils in the dermal papillae, with perivesicular mixed inflammatory infiltrate. Direct immunofluorescence of uninvolved skin is the gold standard. The mainstay of treatment involves a gluten-free diet coupled with the use of medications.Incomplete remission is frequently observed in patients who do not restrict gluten. Conclusion: Knowledge of the clinical and subclinical manifestations of DH and CD as well as laboratory findings is crucial for early diagnosis, helping to rule out misdiagnosis, exacerbations, or complications.